Land Cover Change Model in Sirimau Sub-district, Ambon City, Indonesia - Philia Christi Latue; Yamres Pakniany; Heinrich Rakuasa (Yayasan Adra Karima Hubbi, 2024)
This study aims to analyze the Pattern of Land Cover Change in Sirimau District, Ambon City, Indonesia. The introduction of the research discusses the importance of understanding the dynamic interaction between human activities and land resources in the context of spatially distributed land cover. The research method used was descriptive quantitative with a spatial approach, conducted in Sirimau Sub-district, Ambon City, which experienced high population growth and development of built-up areas. Satellite image data analysis was used to identify patterns of land cover change from 2014 to 2024. The results showed the dominance of agricultural land in 2014, with certain areas converted to residential and built-up land in 2019 and 2024. The findings provide valuable insights in understanding the dynamics of land cover change in Sirimau sub-district and its relevance in sustainable land resource management.